MEN AND WOMEN IN THE TAGNAWA SYSTEM OF ILOCOS (PHILIPPINES) - Norma Adajar Esguerra (SAMPURASUN, 2019)
This research delves into a poverty alleviating way of life of the Ilocanoes- the Tagnawa System. This practice is the coming together of men and women around the neighborhood to help one another during times requiring voluminous work, without thinking monetary remuneration in return. It identified the segment of population that had been practicing it and the occasions in their life as a community that have made this system very fructifying. Data gathering was done through interview with senior citizens in the locality, and reinforced through readings and internet blogs. The tagnawa system was practiced among the Ilocanoes’ of yesteryears: a) on various farming activities, b) on special events like weddings or burials, and c) for house construction, renovation and repair. Focusing on the interview with senior citizens who experienced these three occasions, the researcher was able to identify and appreciate innate Ilocano values and original Iloko terms which are already seldom used nowadays. This research tries to revive their use for the present generation to ponder upon. Indeed, Ilocandia is a place where conscientious people once lived. Let it be forever!